Effect of an Integrated Yoga Regimen on Managing Obesity: A Case Report - Kumar, Santhosh; Palanisamy, Mahalaxmi; Arumugam, Velan; Balakrishnan, Arthi; Ramesh, Vinoth; Sathya, Aravind; Annamalai, Gayathri; Kuppusamy, Maheshkumar (Indian Journal of Integrative Medicine, 2025)
Obesity is a global health concern linked to an increased risk of chronic diseases and reduced quality of life. While conventional treatments primarily emphasize diet and exercise, complementary approaches such as yoga are gaining interest for their potential in weight management. This case report evaluates the effect of an 8 week structured yoga regimen on a 38 year old male with a BMI of 44 kg/m² and a history of unsuccessful weight management through traditional methods. The intervention included daily yoga sessions, incorporating Pawanmuktasana series 3, Nadishodhana pranayama, and quick relaxation techniques, conducted every morning from 7:30 to 8:30 AM and evening from 4:00 to 5:00 PM. The patient experienced significant changes, including weight reduction from 114 kg to 107 kg, a decrease in BMI from 44 kg/m² to 41.3 kg/m², and a reduction in waisthip ratio from 0.92 to 0.86, indicating lower abdominal fat. Improvements in psychological well being, including reduced stress levels and enhanced mood, were also observed. These findings suggest that yoga may serve as a valuable complement to traditional obesity management strategies,promoting both physical and mental health. Further studies are needed to investigate its long term effects in broader populations.